Pascal’s Wager and Theory-Induced Blindness - Haykov, Joseph Mark (Journal of Critical Realism in Socio-Economics (JOCRISE), 2025)
Pascal’s Wager asserts that, based on the descriptions of God in the Bible, an individual is better off believing in the New Testament God than not. This God, referred to as Yahweh in the Torah and as Allah in the Quran, provides a consistent concept of the Biblical God across these texts. Pascal suggests that the hypothesis that the Biblical God is real could turn out to be true. According to the New Testament, Torah, and Quran, it is more beneficial to believe in God than not. From this shared viewpoint, belief leads to heaven, while disbelief, by definition, does not result in heavenly rewards. However, Pascal’s Wager has historically not been taken seriously due to theory-induced blindness. This paper explores this concept in more detail. This paper explores theory-induced blindness as a cognitive bias that influences rational decision-making, particularly in religious and philosophical contexts. By examining its foundations in cognitive psychology, mathematical logic, and set theory, this study highlights the role of implicit axioms in shaping belief systems. It further critiques the dual-hypothesis approach of Pascal’s Wager and discusses its limitations. Through interdisciplinary analysis, this paper demonstrates how unrecognized assumptions can distort logical reasoning, thereby questioning the validity of Pascal’s proposition and its broader implications in decision theory.